Pattern and treatment of Alzheimer’s disease at different health care levels in Bangladesh: a hospital based survey - Hussain Rifat, M. Muhtamim; Parvin, Most. Nazma; Hossain, M. Lokman (International Journal Of Community Medicine And Public Health, 2025)
Background: More than 25 million people in the world today are affected by Alzheimer’s disease. In both developed and developing nations, Alzheimer’s disease (AD) has had tremendous impact on the affected individuals, caregivers, and society. This study investigates the current status of AD in Bangladesh in terms of complications associated with AD as well as treatment strategies. Methods: A cross-sectional design was applied in the study. It involves the formulated questionnaires in four medical namely, Department of Neurology of Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital, National Institute of Neuroscience and Hospital and Alzheimer’s society of Bangladesh from October 2022 to April 2023. Results: Total 153 Alzheimer’s disease patients (male 58.16% and female 41.84%) were recruited in this study. Though the causes of AD are still not fully elucidated, it may be claimed that person having a stressful profession have a high risk to develop AD. From the study, it was noticed that maximum number (73.85%) of patients were identified with manifestations at the moderate signs and symptoms. It was observed that Structural Magnetic Resonance Imaging (sMRI) (97.38%) and Computerized Tomography (CT) scan (93.46%) were most popular diagnosis procedure. It was observed that along with non-pharmacological treatment, drugs used to manage AD were combination of donepezil and memantine (47%), ginkgo biloba (38%), donepezil (9%), rivastigmine (4%) and memantine (2%). However, these drugs also have some adverse effects too. Conclusions: Our population-based data may provide evidence to know about the conditions of AD in Bangladesh.